Low temperature increases adenovirus replication via intracellular alkalization - Sun, Wenwu; Ma, Zhuang; Cao, Jianping; Zhang, Junli (Frontiers in Cellular and Infection Microbiology, 2025)
Changes in environmental temperature contribute to a higher incidence of respiratory tract viral infections during the colder months of the year. However, the effect of low temperature on the replication of viruses in pulmonary epithelial cells is still elusive. In this work, we measured the change of intracellular pH (pHi) and the replication of adenovirus in A549 cells. We observed that exposure of cells to a cooler temperature (33°C) resulted in increases in both intracellular pH and adenovirus replication. In addition, the enhanced replication of adenovirus induced by 33°C was attenuated by inhibition of glycolysis with either 2-deoxy-D-glucose (2-DG) or PFK158. Moreover, oligomycin, which stimulates the glycolytic flux, led to a significant increase in viral replication at 37°C. Further experiments showed that low-temperature-promoted virus replication and intracellular alkalization were efficiently inhibited by the acidification of the extracellular medium. Taken together, these data suggest that intracellular alkalization and glycolysis caused by low temperature enhance adenovirus replication in host cells.